Effect of thiazide on rates of bone mineral loss: a longitudinal study. Issue 6764 (8th December 1990) - Wasnich, R; Davis, J; Ross, P; Vogel, J
Abstract : OBJECTIVE--To determine the effect of thiazide diuretic drugs on rates of bone mineral loss. DESIGN--Longitudinal, observational study with a mean follow up of five years. SETTING--Hawaii Osteoporosis Center, Honolulu. SUBJECTS--1017 Japanese-American men born between 1900 and 1920, of whom 378 were treated for hypertension (study group) and 639 did not have hypertension (control group). INTERVENTION--Thiazide diuretics were taken by 325 men for a mean of 11.9 years; 53 men took antihypertensive drugs other than thiazides. MAIN OUTCOME MEASURE--Rate of bone loss estimated from serial photon absorptiometric scanning at three skeletal sites (calcaneus, distal radius, and proximal radius). RESULTS--Rates of bone loss at all three sites were significantly reduced among thiazide users when compared with controls. The reductions in loss rate ranged from 28.8% (p = 0.02) (distal radius) to 49.2% (p = 0.0005) (calcaneus) relative to the controls. At all three sites the men taking other antihypertensive drugs had faster loss rates (22.6-43.1%) than those of the controls but the difference was significant only for the distal radius. CONCLUSION--Thiazide diuretics slow the rate of bone loss in elderly men.